2005
DOI: 10.1111/j.1365-2591.2005.01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Determining the apical terminus of root‐end resected teeth using three modern apex locators: a comparative ex vivo study

Abstract: Under the conditions of this study all three apex locators were able to detect the apical terminus of root-end resected teeth with an acceptable range. The Root ZX device was the most accurate without over-instrumentation of the root canals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 25 publications
5
62
1
3
Order By: Relevance
“…As a result, different ranges have been used in the evaluation of EAL accuracy. Diverse studies have usually considered the electronic measurements for the minor constriction to be between the 0.5-mm mark (16, 20, 21, 28-30, 32, 33, 35, 36), which is considered highly accurate (37), and the 1-mm mark (24,36,(38)(39)(40). One reason cited for accepting a 1.0-mm margin of error is the wide range seen in the shape of the apical third (21,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, different ranges have been used in the evaluation of EAL accuracy. Diverse studies have usually considered the electronic measurements for the minor constriction to be between the 0.5-mm mark (16, 20, 21, 28-30, 32, 33, 35, 36), which is considered highly accurate (37), and the 1-mm mark (24,36,(38)(39)(40). One reason cited for accepting a 1.0-mm margin of error is the wide range seen in the shape of the apical third (21,41).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with those of the present study in which the file tip was beyond the apical foramen in 51.4% of the canals when the ''APEX'' mark on the dial was used. This fact must be seriously considered because in clinical conditions, in contrast to in vitro studies, a greater variation in measurements is expected because the favorable circumstances for precise measurements are not available (39), and, consequently, an overestimated WL could lead to a poor prognosis (50). These findings raise the question of whether the WL should be established at the point where the EAL indicates the apical foramen or at some distance coronal to that point (33).…”
Section: Discussionmentioning
confidence: 99%
“…Electronic working length determination was influenced by the size of the canal at the apical terminus (2,14,15). Therefore, maxillary central teeth with apical terminus size 30-35 file were chosen to control this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of canal length measurement using electronic apex locators (EALs) is in the range of 80% to 100% as shown by in vitro (3)(4)(5)(6)(7) and clinical studies (6,(8)(9)(10)(11). However, for decades, it has been reported that a number of factors may influence the accuracy of EALs, such as the size of the apical foramen (3,4,6,(12)(13)(14)(15), the type and size of the measuring file (15)(16)(17), the irrigation solution used, and electroconductivity of the pulp (3,4,12,16,18).…”
mentioning
confidence: 99%